Direct Observation of Nucleocytoplasmic Transport by Microinjection of GFP-Tagged Proteins in Living Cells. (August 1999) - Rosorius, O.; Heger, P.; Stelz, G.; Hirschmann, N.; Hauber, J.; Stauber, R.H.
We established a straightforward experimental system to investigate directly the requirements for nucleocytoplasmic transport in live cells. For this purpose, substrates were created containing nuclear localization signals (NLS) or nuclear export signals (NES) linked to a chimeric protein composed of the glutathione S-transferase (GST) fused to the green fluorescent protein (GFP). The combination of GST/GFP-tagging allowed us to control protein expression in bacteria and to monitor protein purification during chromatography. Following microinjection into somatic cells, nuclear export/import of the highly fluorescent substrates could be observed directly by fluorescence microscopy. This system sets the stage to quantitate, in real time, the kinetics of nuclear import/export in living cells and to evaluate qualitative differences in various NLS/NES signals and pathways.